2013
DOI: 10.1103/physrevlett.110.198101
|View full text |Cite
|
Sign up to set email alerts
|

Distance Matters: The Impact of Gene Proximity in Bacterial Gene Regulation

Abstract: Following recent discoveries of colocalization of downstream-regulating genes in living cells, the impact of the spatial distance between such genes on the kinetics of gene product formation is increasingly recognized. We here show from analytical and numerical analysis that the distance between a transcription factor (TF) gene and its target gene drastically affects the speed and reliability of transcriptional regulation in bacterial cells. For an explicit model system, we develop a general theory for the int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 51 publications
(41 reference statements)
3
109
0
Order By: Relevance
“…It is also possible that the molecular crowding or highly condensed DNA in the cell make the binding of TFs more favorable as mentioned in several reports [66][67][68]. Especially, in the case of prokaryotic cells, the TF gene and its target sequence are frequently colocalized, resulting in the acceleration of the target search [69][70][71]. Further investigations based on the quantitative comparison of in vitro and in vivo data must be conducted to elucidate the components involved in the activation of p53.…”
Section: Discussionmentioning
confidence: 95%
“…It is also possible that the molecular crowding or highly condensed DNA in the cell make the binding of TFs more favorable as mentioned in several reports [66][67][68]. Especially, in the case of prokaryotic cells, the TF gene and its target sequence are frequently colocalized, resulting in the acceleration of the target search [69][70][71]. Further investigations based on the quantitative comparison of in vitro and in vivo data must be conducted to elucidate the components involved in the activation of p53.…”
Section: Discussionmentioning
confidence: 95%
“…Our study suggests that stochastic hybrid schemes will be useful tools for exploring large scale genetic networks, which display complex multi-attractor dynamics caused by discrete fluctuations in the promoter architecture and should find their place alongside more traditional full scale kinetic Monte Carlo simulations. For future work, it would be interesting to use such hybrid schemes to model the effects of gene colocalization, [68][69][70] heterogeneous distribution of transcription factors in nuclear/cytoplasmic milieu, 71 and 1D/3D diffusional motions 72,73 by adding additional deterministic steps for each molecular component and enlarging the number of internal discrete promoter states. The latest studies have shown that in eukaryotic cells gene expression is an intricate function of chromatin configuration as well as spatial distribution of decoy binding sites on the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, effects of the crowded cytoplasm of living cells were considered by different approaches in [101,102]. A path integral formulation of the downregulation of one gene by the product of a steering gene, including the stochasticity of the regulation process [103] was given in [104]. A noteworthy result of that study is that the efficiency of the protein search for its target binding site crucially depends on the initial distance from this target [104], a result that is consistent with the so-called rapid search hypothesis based on bioinformatics research [1].…”
Section: Search Along Dna Chainsmentioning
confidence: 99%